A 7.5‐μW 0.08‐mm2 single‐ended SC delta‐sigma ADC for acoustic sensor applications. (16th September 2015) - Duan, Quanzhen; Wang, Zhidong; Roh, Jeongjin
Summary: This study presents an ultra‐low‐power, small‐size, 1‐bit, single‐ended, and switched‐capacitor (SC) delta‐sigma analog‐to‐digital converter (ADC) for wireless acoustic sensor nodes. This wireless sensor node has a delta‐sigma ADC that converts the sensed signal to a digital signal for convenient data processing and emphasizes the features of small size and low‐power consumption. The chip area of the delta‐sigma ADC is dominated by the capacitor; therefore, a novel common‐mode (CM) controlling technique with only transistors is proposed. This ADC achieves an extremely small size of 0.08 mm 2 in a 130‐nm CMOS process. The conventional operational transconductance amplifiers (OTAs) are replaced by inverters in the weak inversion region to achieve high power efficiency. At 4‐MHz sampling frequency and 0.7‐V power supply voltage, the delta‐sigma ADC achieves a 55.8‐dB signal‐to‐noise‐plus‐distortion ratio (SNDR) and a 298‐fJ/step figure‐of‐merit (FOM) in a signal bandwidth of 25 kHz, while consuming only 7.5 μW of power. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In wireless sensor node, low power and small size are main requirement for the components, so an ultra‐low‐power and small size delta‐sigma ADC is designed for the acoustic sensor application. Because of the novel common‐mode control technique without using capacitors, extremely small size of 0.08 mm 2 is obtained. Inverter‐based OTAs working in weak‐inversion region are used and achieve high power efficiency, and the proposed delta‐sigma ADC consumes only 7.5 μW.